The impact of preoperative anemia on postoperative anemia and related nutritional abnormalities after bariatric surgery: a multicenter cohort study - Nie, Yuntao; Ping, An; Liu, Baoyin; Meng, Hua (Frontiers in Nutrition, 2025)
BackgroundAnemia is a common nutritional complication after bariatric surgery, deteriorating quality of life. Despite 10–30% of patients with obesity being anemic preoperatively, current guidelines do not recommend managing anemia before surgery. This study aims to evaluate the impact of preoperative anemia on postoperative anemia and related nutritional abnormalities.MethodsPatients undergoing bariatric surgery at two bariatric centers from 2017 to 2021 were reviewed and followed for 1 year. Anemia was defined by WHO criteria. Nutritional abnormalities included ferritin, folate, and vitamin B12 deficiency, and low transferrin saturation (TS) levels.ResultsA total of 452 patients were included, of whom 53 (11.7%) were diagnosed with anemia before surgery. Patients with preoperative anemia were more likely to develop postoperative anemia (69.8% vs. 34.8%, p < 0.001), ferritin deficiency (77.4% vs. 41.6%, p < 0.001), and low TS levels (56.6% vs. 20.3%, p < 0.001) than normal patients. Changes in hemoglobin, ferritin, folate, and vitamin B12 levels did not differ significantly between patients with preoperative anemia and normal patients. After fully adjusting for covariates, preoperative anemia was independently associated with postoperative anemia (OR 3.52, 95% CI 1.83–7.06, p < 0.001), moderate to severe anemia (OR 5.03, 95% CI 2.48–10.20, p < 0.001), ferritin deficiency (OR 3.77, 95% CI 1.74–8.17, p = 0.001), and low TS levels (OR 4.12, 95% CI 2.16–7.84, p < 0.001).ConclusionPreoperative anemia significantly elevates the risk of postoperative anemia, especially moderate to severe cases, and increases the incidence of iron deficiency. It is crucial to actively screen for and correct preoperative anemia to enhance hemoglobin levels and prevent postoperative anemia.